In vitro culture of Annona emarginata: a rootstock for commercial annonaceae species - Freitas, R.T. de; Paiva, R.; Campos, N.A.; Silva, L.C.; Swennen, Rony L.; Panis, Bartholomeus (2016)
Annona emarginata is a native fruit tree in the Brazilian Cerrado which, unlike the commercial species, does not present a high fruit quality. On the other hand, it stands out based on its rootstock value. However, there are some problems that hinder the largescale production of Annona emarginata seedlings for use as a rootstock. In order to overcome these difficulties, micropropagation has become a viable alternative for the rapid and efficient propagation of Annona spp, but Annona emarginata micropropagation has not yet been reported. Therefore, the aim of this study was to initiate Annona emarginata in vitro growth. For axillary shoot proliferation, in vitro nodal segments of 0.5 cm were transferred to MS or WPM supplemented with BA at different concentrations. Nodal segments were also cultured on WPM medium with ranging concentrations of different plant growth regulators, aiming for either shoot elongation or rooting. The results showed that the use of 1 µM BA in WPM medium is recommended for in vitro multiplication of Annona emarginata. This is based on the low adventitious shoot formation, combined with a higher number of buds and leaves. The use of GA3 at any concentration tested induced the formation of malformed plants. Root formation could not be stimulated, regardless the duration of auxin treatment.